Critical Delay Factors in PHJD Road Construction Project: A Case Study in North Toraja Using the Relative Importance Index (RII) Method - Ibrahim, Zulfadli; Muis, Ulmiah; Yunus, Ilham; Afiah, Indah Nur (Universitas Negeri Makassar, 2025)
This study aims to analyse the critical factors causing delays in the Provincial Road Grant Program (PHJD) road construction project in North Toraja Regency, particularly on the Pangala-Baruppu-West Sulawesi road segment, using the Relative Importance Index (RII) method. Data were collected through questionnaires completed by 34 respondents directly involved in the project, including contractors, supervising consultants, and other related parties. The results of the study show that the most significant cause of delays in the PHJD road construction project was material testing delays, with the highest RII score of 0.888. Other key contributors were material delivery issues, ineffective coordination, and unpredictable weather. Financial issues had a medium impact, while factors like low labor productivity and lack of GS responsibility were less influential. Design changes and land acquisition were the least significant. The findings emphasize the need for improved coordination, efficient material handling, and better preparation for environmental challenges to minimize delays and enhance project performance.